Drought stress in Maize (Zea mays L.) : effects, resistance mechanisms, global Achievements and biological strategies for improvement /: effects, resistance mechanisms, global Achievements and biological strategies for improvement. (2015) - (Plant scientist), Aslam, Muhammad; Maqbool, M. A (Muhammed Ahmed), 1941-; Cengiz, Rahime, 1974-
No abstract available